The Relationship Between Fraud Hexagon and Corruption - Pradnyani, I Dewa Ayu Agung Oka; Sukartha, Putu Dyan Yaniartha; Widhiyani, Ni Luh Sari; Ratnadi, Ni Made Dwi (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Corruption is notably the most prevalent in Indonesia. State-Owned Enterprises (SOEs) represent the second most affected sector by fraudulent activities. This study aims empirically examine the relationship between the elements of the fraud hexagon and corruption. The research focuses on SOEs listed on the Indonesia Stock Exchange between 2001 and 2023, 459 observations were selected using a purposive sampling technique. Data were collected through documentation methods and analyzed using multiple logistic regression analysis. The analyzed result reveal that pressure and rationalization show a negative relationship with corruption. Opportunity and collusion show a positive relationship with corruption. The capability and ego element, however, does not exhibit a significant relationship with corruption. These results provide additional insights and empirical evidence on how opportunity and collusion contribute to corruption. Furthermore, the implications of this study offer meaningful contributions to SOEs, investors, prospective investors, and policymakers, supporting efforts to strengthen governance and prevent corruption in key public sector institutions.